Improving Learning Environments : School Discipline and Student Achievement in Comparative Perspective. - Arum, Richard (Studies in social inequality., 2012)
Improving Learning Environments provides the first systematic comparative cross-national study of school disciplinary climates. In this volume, leading international social science researchers explore nine national case studies to identify the institutional determinants of variation in school discipline, the possible links between school environments and student achievement, as well as the implications of these findings for understanding social inequality. As the book demonstrates, a better understanding of school discipline is essential to the formation of effective educational policies. Ulti.